2011
DOI: 10.1002/eji.201041137
|View full text |Cite
|
Sign up to set email alerts
|

A dose‐dependent role for EBF1 in repressing non‐B‐cell‐specific genes

Abstract: Summary In the absence of EBF1, B cell development is arrested at an uncommitted progenitor stage that exhibits increased lineage potentials. Previously, we investigated the roles of EBF1 (E) and its DNA binding partner Runx1 (R) by evaluating B lymphopoiesis in single (Ehet and Rhet) and compound haploinsufficent (ERhet) mice. Here, we demonstrate that reduced Ebf1 gene dosage results in the inappropriate expression of NK cell lineage-specific genes in B cell progenitors. Moreover, prolonged expression of Ly6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
1
35
2
Order By: Relevance
“…Also interesting with regard to leukemia development is the finding that reduced transcription factor dose may result in lineage plasticity in B-cell progenitors. Although our functional analysis did not reveal any dramatic increase in lineage instability of B-lineage cells, it has been reported that monoallelic loss of Ebf1 leads to aberrant expression of NK-lineage genes in B-lymphoid progenitors (22). This indicates that alternative lineage programs cannot be properly silenced, and it should not be excluded that combined heterozygote deletions of Pax5 and Ebf1 may impact lineage commitment in a more dramatic manner than the heterozygote loss of either of these proteins alone.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Also interesting with regard to leukemia development is the finding that reduced transcription factor dose may result in lineage plasticity in B-cell progenitors. Although our functional analysis did not reveal any dramatic increase in lineage instability of B-lineage cells, it has been reported that monoallelic loss of Ebf1 leads to aberrant expression of NK-lineage genes in B-lymphoid progenitors (22). This indicates that alternative lineage programs cannot be properly silenced, and it should not be excluded that combined heterozygote deletions of Pax5 and Ebf1 may impact lineage commitment in a more dramatic manner than the heterozygote loss of either of these proteins alone.…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, low levels of PAX5 expression in hematopoietic progenitors result in an expansion of cells expressing a combination of myeloid and lymphoid genes similar to what can be observed in biphenotypic leukemia (19). Functional transcription factor dose is also of crucial importance in normal B-cell development, where reduced levels of E-proteins (E2A, HEB, and E2-2) (20) or loss of one allele of Ebf1 alone or in combination with E2a or Runx1 results in disturbed B-cell development (5,(21)(22)(23). Hence, transcription factor dose is of critical importance for malignant transformation in leukemia as well as normal B-cell differentiation, creating a link between development and disease.…”
mentioning
confidence: 77%
“…[6][7][8] Ebf1 levels are also of relevance in leukemia because mutations resulting in reduced functional EBF1 dose 9,10 and increased expression of post-transcriptional inhibitors of EBF1, ZNF521, 11 or ZNF423 12 are found in B-cell acute lymphoblastic leukemia (B-ALL). 13,14 A direct role for Ebf1 dose in malignant transformation was supported by the findings that combined expression of constitutively active Stat5 (caStat5) and heterozygous loss of either Ebf1 or Pax5 results in B-cell leukemia in mice.…”
Section: Cd43mentioning
confidence: 99%
“…These findings are partially overlapping with the phenotype observed in Ebf1 and Pax5 knockout mice, where it has been shown that EBF1 and PAX5 are critical regulators of B-lineage specification and commitment by repressing alternative non-B-cell fates. [13][14][15] As the expression of Ebf1 and Pax5 itself is not inhibited in Btg1 -/-…”
Section: ;Btg2mentioning
confidence: 97%